2010
DOI: 10.5194/nhess-10-139-2010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 1755-like tsunami in Huelva, Spain

Abstract: Abstract. Coastal areas are highly exposed to natural hazards associated with the sea. In all cases where there is historical evidence for devastating tsunamis, as is the case of the southern coasts of the Iberian Peninsula, there is a need for quantitative hazard tsunami assessment to support spatial planning. Also, local authorities must be able to act towards the population protection in a preemptive way, to inform "what to do" and "where to go" and in an alarm, to make people aware of the incoming danger. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
3
27
0
1
Order By: Relevance
“…A TIN (Triangular Irregular Network) with all these data points, including the zero height line as constraints and break-lines representing surface discontinuities close to the shoreline (harbor, pier, quay), was constructed. The procedures were similar to those described in Lima et al (2010), where the accuracy of the grid was evaluated as better than 0.5 m inland. Offshore the swath bathymetry data has an accuracy depth dependent which can be considered as compatible with on-shore data.…”
Section: Dem Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A TIN (Triangular Irregular Network) with all these data points, including the zero height line as constraints and break-lines representing surface discontinuities close to the shoreline (harbor, pier, quay), was constructed. The procedures were similar to those described in Lima et al (2010), where the accuracy of the grid was evaluated as better than 0.5 m inland. Offshore the swath bathymetry data has an accuracy depth dependent which can be considered as compatible with on-shore data.…”
Section: Dem Developmentmentioning
confidence: 99%
“…Previous tsunami simulations by Baptista et al (2003) and Gutscher et al (2006) and recent inundation studies in the area used these scenarios (see Omira et al, 2010;Lima et al, 2010) have showed the individual properties of such tsunami sources: the GF fault, located north of the Gorringe bank, radiates most energy towards North America and Morocco; the PB fault being almost parallel to the South Portuguese coast is not effective in producing a devastating tsunami along the west coast of Portugal, where Lisbon is located. The CW is the biggest structure identified in the area which is very effective in radiating energy towards the Strait of Gibraltar, but it seems unable to explain the tsunami observed on the west coast.…”
Section: Introductionmentioning
confidence: 99%
“…This area of tectonic deformation is responsible for the offshore seismicity of south-western Iberia. The worst cases, as well as the fault traces that we used for the Cadiz Bay area, are described in Lima et al (2010), and their summary is presented in Table 3, A more detailed description of the tSllllami sources is provided in DC-IGN (2009) and DCA (2009). The tSllllami risk was only estimated for the population distributed in 112 municipal districts of Cadiz.…”
Section: Scope Defi Nitionmentioning
confidence: 99%
“…The tsunami hazard in the Gulf of Cadiz region, which is an important component of a TWS, is well established through the elaboration of the historical tsunami catalogs Kaabouben et al, 2009;Blanc, 2009), the definition of the tsunamigenic scenarios (Omira et al, 2009), the identification of tsunami deposits (Ruiz et al, 2005;Font et al, 2010;Medina et al, 2011;Costa et al, 2011), and the estimations of the waves' impact Lima et al, 2010;Baptista et al, 2011a). Moreover, major efforts have been addressed to enhance the seismic network to cover areas around the Azores-Gibraltar plate boundary, and in particular the Cadiz Gulf region.…”
Section: R Omira: Performance Of Sea-defense Structures In Morocco Amentioning
confidence: 99%
“…In the Gulf of Cadiz coastal areas, various studies have been addressed to investigate tsunami impact (Lima et al, 2010;Omira et al, 2011;Baptista et al, 2011a), and the area's vulnerability . These works and this paper show the high level of destruction that coastal areas of Morocco, Portugal and Spain could experience following the occurrence of large regional tsunami events, and hence the need for robust TWS in the region to mitigate the tsunami hazard.…”
Section: The Need Of Tsunami Preparedness and Warning System In The Rmentioning
confidence: 99%